Does the household structure influence remuneration in Poland? - Witkowska, Dorota (Czy struktura gospodarstw domowych wpływa na wynagrodzenia w Polsce?, 2018)
The main income determinants are: general economic situation, individual attributes of employees and characteristics of the workplace. However, there are also family duties which affect economic activity and wages, mostly in case of women who are the main care providers to children, the elderly, handicapped or sick. The aim of our research is to find out if the structure of the households influences the monthly remuneration of employees in Poland. The investigation consists in estimation econometric models which describe monthly remuneration on the basis of the microdata. Research is provided for the sample of employees regardless of gender, separately for male and female employees, and for women in three age classes. The analysis based on econometric models enables to find out that on average: (1) male employees earn significantly more than females, (2) married women earn less than unmarried ones while in case of men the situation is the opposite, (3) the motherhood penalty exists in Poland and (4) care providers for the elderly are mostly women, and care duties influence mostly remuneration received by women aged 25-54.
Econometrics = Ekonometria, 2018, Vol. 22, No. 4, s. 24-42
Keywords: gender wage disparities; remuneration; structure of the household